Metode Penulisan Naskah Kolektif: Di Balik Pertunjukan Teater “Tanah Ode Kampung Kami” - Iman Soleh; Mahesa El Gasani; Mazeinda Al Biruni; Tari Purwanti (Umbara, 2021)
The creation of a play entitled “Tanah Ode Kampung Kami” have several stages, starting from determining the issue and the ideas, conducting research, implementing the method of collective writing text, and finally becomes a show. The research process is a way of organizing and understanding the main problem of a play, i.e. the land, so it would be able to be implemented as a drama script collectively in theatrical performances. Collective text aims to make actors and directors have the same perception of a predetermined theme. This study uses a qualitative research design with data collection methods in the form of observations and interviews. The conclusion of this study is that the collective text method used in the “Tanah Ode Kampung Kami” script is used to harmonize the ideas that were built together so that it becomes a complete text which is the result of collaborative thinking between the elements involved in the process of making the script.